HUBUNGAN PERAN ORANG TUA DALAM ANTICIPATORY GUIDANCE SIBLING RIVALRY DAN KECERDASAN EMOSIONAL DENGAN KEJADIAN SIBLING RIVALRY PADA ANAK USIA PRASEKOLAH - Ulva Noviana (NHM PRESS, 2019)
Sibling rivalry is the natural jealousy or dislike feeling of a children to a new child in the family. Preliminary study result obtained 6 (60%) children have sibling rivalry. The purpose of the study was to analyze the relationship of parent role in anticipatory guidance sibling rivalry and emotional intelligence with sibling rivalry incident in preschooler. The design of this research is correlational analytic with cross sectional approach. The independent variable is the parent role in the anticipatory guidance sibling rivalry and emotional intelligence, while the dependent variable is sibling rivalry. The unit of analysis of this study is preschool children who have younger siblings, and the source of information is parents, the sample of 37 children with simple random sampling technique. The data collected from these three research variables used questionnaires. The statistical test using spearman rank with α (0,05). The result of the statistical test shows the value of p value with the alpha significance level α (0,05), mean value of p value < α, so H0 is rejected and H1 accepted, it means there is relation of parent role in anticipatory guidance sibling rivalry and emotional intelligence with incident sibling rivalry preschooler. The results of this study is expected parents can perform its role in anticipatory sibling rivalry and improve the emotional intelligence of children to avoid sibling rivalry between siblings